Proceedings of the Companion Publication of the 17th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computi 2014
DOI: 10.1145/2556420.2556503
|View full text |Cite
|
Sign up to set email alerts
|

Understanding in-situ social media use at music festivals

Abstract: Participation at large music festivals is changing, with many attendees using social media platforms to mediate and shape their experiences of attending such events. We used a combination of Twitter and Foursquare to collect social media posts from attendees at the Glastonbury 2013 music festival and performed a thematic analysis in order to better understand the insitu use of such media. Our findings reflect the wide range of users' purposes in such settings and provides a basis for further exploration of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The time-distribution profiles for Twitter use, as mentioned above, indicate that Twitter is a ‘here-and-now’ medium, in accordance with previous research into Twitter use in political campaigns (Larsson and Moe, 2012). There is little research into Twitter use during concerts, but our findings resonate with previous studies by Bennett (2012, 2014) and Jamison-Powell et al (2014), as well as unpublished studies of tweeting at Øya 2011 (Maasø, 2012) and the by:Larm festival in 2011 (Vestli et al, 2011). Both found that ‘here-and-now’ tweets were predominant, and, moreover, that tweets were typically instant reactions to the live concert event or its atmosphere.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The time-distribution profiles for Twitter use, as mentioned above, indicate that Twitter is a ‘here-and-now’ medium, in accordance with previous research into Twitter use in political campaigns (Larsson and Moe, 2012). There is little research into Twitter use during concerts, but our findings resonate with previous studies by Bennett (2012, 2014) and Jamison-Powell et al (2014), as well as unpublished studies of tweeting at Øya 2011 (Maasø, 2012) and the by:Larm festival in 2011 (Vestli et al, 2011). Both found that ‘here-and-now’ tweets were predominant, and, moreover, that tweets were typically instant reactions to the live concert event or its atmosphere.…”
Section: Discussionsupporting
confidence: 90%
“…3 Bennett (2012) finds that tweeting and texting is used to broaden the fan community at live concerts and include fans that are not present at the event, for example, by tweeting the set-list of the concert or commenting on the performance on stage. Also Jamison-Powell et al (2014) found widespread use of Twitter among the audience during live music concerts. All these resonate well with research into the Twitter use that surrounds political election campaigns, which also points towards spikes in tweeting as representative of an immediate response to an event (in that case, events in the mainstream media; Larsson and Moe, 2012).…”
Section: The Mediated Festivalmentioning
confidence: 99%
“…Previous CSCW research has explored how digital technologies can enhance audience interaction with live performance, including delivering interactive concert programmes on personal devices [6]; contributing to shared visual projections by drawing using mobile phones and dancing [48]; being directed to film the performance from different angles [47]; and the wider user of social media around festivals [25]. One relevant concept to emerge from this work is that of designing an extended audience journey through interactive performances, spanning ticketing, pre-show activities, intervals, and even post show reflection, beyond those moments when the show is occurring onstage.…”
Section: Online Performancesmentioning
confidence: 99%
“…According to Mills et al (2012), data analytics is defined as “large volumes of high velocity, complex and variable data that require advanced techniques and technologies to enable the capture, storage, distribution, management, and analysis of the information.” Although few studies have examined data analytics in the context of music festivals and have focused mainly on festivals in the USA, UK and Europe, examples from previous studies are used as references in this study. For example, Jamison-Powell et al (2014) investigated how festival goers used Twitter and Foursquare while attending the Glastonbury Music Festival (UK) in 2013. de Lira et al (2017) developed a process to predict event attendance using machine learning at the Creamfields and VFestival music festivals in the UK.…”
Section: Literature Reviewmentioning
confidence: 99%